Relating rice grain quality to conditions during sun drying - Meas, Pyseth; Paterson, Anthony Henry John; Cleland, Donald J.; Bronlund, John E.; Mawson, John; Hardacre, Allan; Rickman, Joseph Frederick (Walter de Gruyter GmbH, 2013)
Rice grain conditions within the sun-drying bed predicted by a mathematical model during drying were used to relate drying parameters to the head rice yield (HRY) which is the key rice quality metric. A number of parameters were derived to characterise the mechanisms of grain fissures and breakage postulated in the literature, and the model was used to estimate these parameters. These parameters were then regressed against the HRY experimental data to determine the contributing mechanisms. An increase in bed temperature, the maximum temperature at the top of the bed, the size of the moisture content gradients within a rice grain and the difference from the critical point for drying were all found to negatively affect HRY. By stirring the bed regularly and covering and shading the bed during the hottest parts of the day, HRY can be significantly increased leading to better returns to the farmer.